2022
DOI: 10.21462/jeltl.v7i3.892
|View full text |Cite
|
Sign up to set email alerts
|

The Portrait of Challenges in Teaching English to Young Learners: A Case Study in an Indonesian Islamic School

Abstract: <em>Teaching English to students with no prior knowledge, a different first language, and varied characters is challenging. This research is a case study design that focused on the teachers’ perceptions of teaching English to young learners situated in one of the Islamic schools in Malang, Indonesia. The participants involved were six English teachers at the chosen school. A qualitative approach was employed in this study.  Data were generated through interviews. Findings suggest that the participating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Many researches have shown the difficulties in teaching English, particularly to young students, as well as the potential of qualitative research for addressing these challenges. Pertiwi et al, (2022) and Copland et al, (2014) identified and investigated these obstacles, which included non-English prior knowledge, a lack of wants, and an unpleasant classroom setting, using qualitative methodologies. Wang (2018) and Weinberger (2018) emphasize the value of qualitative research in the field of English language teaching and learning, noting its capacity to capture the challenges of educational contexts.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researches have shown the difficulties in teaching English, particularly to young students, as well as the potential of qualitative research for addressing these challenges. Pertiwi et al, (2022) and Copland et al, (2014) identified and investigated these obstacles, which included non-English prior knowledge, a lack of wants, and an unpleasant classroom setting, using qualitative methodologies. Wang (2018) and Weinberger (2018) emphasize the value of qualitative research in the field of English language teaching and learning, noting its capacity to capture the challenges of educational contexts.…”
Section: Methodsmentioning
confidence: 99%
“…This study will contribute to understanding on how to address the challenges identified in teaching English at SDN Mangunsari. In previous study, as in Pertiwi et al (2022) study on challenges in teaching English on young learner, has explored the difficulties encountered during teaching English in primary level. However, in this study, the author aims to not only identify the challenges, but also to propose a way to addres these issues.…”
Section: Introductionmentioning
confidence: 99%
“…The research findings shed light on the strategies employed by teachers to effectively navigate cross-teaching activities and enhance students' engagement with English materials. Some previous research concludes that EYL teachers should be engaging the student's interest in teaching English to young learners (Adipat et al, 2021;Mamat et al, 2023;Pertiwi et al, 2022). Similarly, Eka, who is involved in musical composition and game development, asserted that both music and games have the capacity to foster active involvement among students and enhance their participation in the learning process.…”
Section: Teachers' Strategiesmentioning
confidence: 99%
“…There are two journals that are related to this article. The first article is from Pertiwi (2022), in her article, she discussed the obstacle to teaching English to young learners. At this time, this article also wants to discuss the teachers' strategies for teaching young learners.…”
Section: Introductionmentioning
confidence: 99%